Fluorescent DNA Stabilized Silver Nanoclusters as Biosensors - Alfonso Latorre; Romina Lorca; Álvaro Somoza (Journal of Chemistry)
DNA stabilized fluorescent silver nanoclusters are promising materials, of which fluorescent properties can be exploited to develop sensors. Particularly, the presence of a DNA strand in the structure has promoted the development of gene sensors where one part of the sensor is able to recognize the target gene sequence. Moreover, since oligonucleotides can be designed to have binding properties (aptamers) a variety of sensors for proteins and cells have been developed using silver nanoclusters. In this review the applications of this material as sensors of different biomolecules are summarized.